A graphene-like Mg3N2 monolayer: high stability, desirable direct band gap and promising carrier mobility. Issue 44 (27th October 2016) - Liu, Peng-Fei; Zhou, Liujiang; Frauenheim, Thomas; Wu, Li-Ming
Abstract : A novel two-dimensional material, g-Mg3 N2, exhibits an intrinsic direct band gap of 1.86 eV, outstanding stability (2000 K) and a high carrier mobility of up to 10 3 cm 2 V −1 s −1 which is larger than that of MoS2 and close to that of few-layer phosphorene. Abstract : Based on density functional calculations and a global particle-swarm optimization method, a novel Mg3 N2 monolayer (g-Mg3 N2 ) with a hexagonal lattice was firstly predicted, displaying an intrinsic direct band gap of 1.86 eV, close to that (1.90 eV) of a MoS2 monolayer. In the infinite planar geometry, each N atom adopts sp 2 hybridization with three Mg atoms and each Mg atom as a 2-fold coordinated "bridge" enables the stable bonding with two N atoms. Such a g-Mg3 N2 sheet is not only dynamically stable, but also can withstand temperatures up to 2000 K. Importantly, the intrinsic acoustic-phonon-limited carrier mobility of the g-Mg3 N2 sheet can reach ∼10 3 cm 2 V −1 s −1 for electrons and ∼433 cm 2 V −1 s −1 for holes under ambient conditions, higher than that (60–200 cm 2 V −1 s −1 ) of MoS2 and comparable to that (∼10 3 cm 2 V −1 s −1 ) of few-layer phosphorene. In particular, the derivative nanotubes have direct band gaps, independent of chirality and radius. The versatility of g-Mg3 N2 and its derivatives is expected to possess a broad range of applications in FET devices.